Detection and investigation of carbon ions induced by ND:YAG laser using SSNTDS - Qindeel, Rabia (American Institute of Physics, 2011)
A Q-Switched Nd:YAG laser pulse of pulsed width of 9~14 ns, wavelength of 1064 nm, repetition rate of 0.5 Hz, power of 1.1 MW and energy of 10 mJ has been used to ablate the 4N pure graphite target through IR lens. Solid state nuclear track detector (SSNTD) CR-39 has been used to calculate the energy of carbon ions produced as a result of laser ablation and the whole experiment has been performed under pressure ~10-3 Torr in stainless steel vacuum chamber. The minimum and maximum energy of carbon ions observed are 0.2 KeV to 250 KeV respectively.